2018
DOI: 10.3386/w24300
|View full text |Cite
|
Sign up to set email alerts
|

Making Big Changes: The Impact of Moves on Marriage among U.S. Army Personnel

Abstract: H2D2 conference. All errors are of course our own. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Hogan and Seifert (2010) find that marriage itself is more common for young active-duty military service members, compared with similar civilians, and that the odds of divorce are also greater after two years of service, compared with civilians. Carter and Wozniak (2018) show that relocations, such as permanent change of station moves, are strongly associated with increased marriage rates. Together, the research suggests that the decision to get married and stay married and the decision to serve and remain in service are intertwined.…”
Section: Attrition Of Married Recruitsmentioning
confidence: 96%
“…Hogan and Seifert (2010) find that marriage itself is more common for young active-duty military service members, compared with similar civilians, and that the odds of divorce are also greater after two years of service, compared with civilians. Carter and Wozniak (2018) show that relocations, such as permanent change of station moves, are strongly associated with increased marriage rates. Together, the research suggests that the decision to get married and stay married and the decision to serve and remain in service are intertwined.…”
Section: Attrition Of Married Recruitsmentioning
confidence: 96%
“…Furthermore, assignments "will not be influenced by the employment, school enrollment, volunteer activities, or health of a Service member's family member" (DoD 2015). Several papers have demonstrated that the timing and frequency of relocations is not subject to soldier preferences, including Lyle (2006), Lleras-Muney (2010), Skimmyhorn (2017), andWozniak (2018). Moves within a catchment area may be endogenous since they are unlikely to be driven by personnel management needs; we therefore exclude such moves from our analysis.…”
Section: Part I: Institutional Backgroundmentioning
confidence: 99%